Grid-Connection Half-Bridge PV Inverter System for Power Flow Controlling and Active Power Filtering - Chih-Lung Shen; Jye-Chau Su (International Journal of Photoenergy)
A half-bridge photovoltaic (PV) system is proposed, which can not only deal with bidirectional power flowing but also improve power quality. According to varying insolation, the system conditions real power for dc and ac loads to accommodate different amounts of PV power. Furthermore, the system eliminates current harmonics and improves power factor simultaneously. As compared with conventional PV inverter, the total number of active switches and current sensors can be reduced so that its cost is lower significantly. For current command determination, a linear-approximation method (LAM) is applied to avoid the complicated calculation and achieve the maximum power point tracking (MPPT) feature. For current controlling, a direct-source-current-shaping (DSCS) algorithm is presented to shape the waveform of line current. Simulation results and practical measurements also demonstrate the feasibility of the proposed half-bridge PV system.